First coeds to qualify for the loyalty award - Magno, Ma. Cristina Ana (Animo Repository, 1992)
For the first time in the history of the University, Biology majors Ma. Cristina Ana Magno and Ma. Celeste Sicat, graduates of La Salle-Zobel, become the first coeds to qualify for the loyalty award.